INTEGRASI COGNITIVE LOAD THEORY DAN PEMBELAJARAN MULTISENSORIK: KERANGKA NEURO-KOGNITIF UNTUK OPTIMALISASI PEMAHAMAN DAN KETERLIBATAN SISWA DI ERA DIGITAL - Wasi, Ramlan Abdul; Ismail, Shalahudin; Mulyadi, Yadi; Rindiani, Ani (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study explores the integration of Cognitive Load Theory (CLT) and multisensory learning to enhance cognitive understanding and student engagement in the digital age. Through a systematic analysis of 45 literature sources (2018–2024), a Neuro-Cognitive Load framework was developed that combines principles from cognitive psychology and neuroscience. Findings indicate that this integrated approach reduces external load by 32% through optimal visual-auditory presentation (<7 minutes), while activating brain regions associated with multisensory processing. At the practical level, the combination of worked examples and haptic simulations enhances STEM knowledge transfer by 41%. Cognitive impacts include improved retention (55%), reduced conceptual errors (38%), and enhanced knowledge transfer (29%). Student engagement analysis shows increased attention focus (73%), positive affect (M=4.2 vs 3.1), and active participation (2.3× higher). Implementation challenges include resource limitations (85% of teachers experienced technical difficulties) and student diversity, addressed through low-tech solutions (audio-enhanced diagrams) and teacher training (ES=0.89). The study’s conclusions emphasize the synergy of CLT-multisensory when it meets: (1) precise design aligned with cognitive capacity, (2) varied stimulation, and (3) contextual adaptation. The main implication is the need for educators to act as skilled cognitive designers who integrate neuroscience with pedagogical practices. Recommendations include developing a phased implementation protocol and further research on adaptive systems based on cognitive profiles. ABSTRAKPenelitian ini mengeksplorasi integrasi Cognitive Load Theory (CLT) dan pembelajaran multisensorik untuk meningkatkan pemahaman kognitif dan keterlibatan siswa di era digital. Melalui analisis sistematis terhadap 45 literatur (2018-2024), dikembangkan kerangka Neuro-Cognitive Load yang menggabungkan prinsip psikologi kognitif dan neurosains. Temuan menunjukkan pendekatan terintegrasi ini mengurangi beban eksternal 32% melalui penyajian visual-auditori optimal (<7 menit), sekaligus mengaktifkan area otak terkait pemrosesan multisensorik. Pada tingkat praktis, kombinasi worked examples dan simulasi haptik meningkatkan transfer pengetahuan STEM 41%. Dampak kognitif mencakup peningkatan retensi (55%), penurunan kesalahan konseptual (38%), dan peningkatan transfer pengetahuan (29%). Analisis keterlibatan siswa menunjukkan peningkatan fokus perhatian (73%), positive affect (M=4.2 vs 3.1), dan partisipasi aktif (2.3× lebih tinggi). Tantangan implementasi termasuk keterbatasan sumber daya (85% guru mengalami kesulitan teknis) dan keragaman siswa, yang diatasi melalui solusi low-tech (audio-enhanced diagram) dan pelatihan guru (ES=0.89). Kesimpulan penelitian menggarisbawahi sinergi CLT-multisensorik ketika memenuhi: (1) desain presisi sesuai kapasitas kognitif, (2) variasi stimulasi, dan (3) adaptasi kontekstual. Implikasi utama adalah perlunya pendidik berperan sebagai desainer kognitif yang terampil mengintegrasikan neurosains dengan praktik pedagogis. Rekomendasi mencakup pengembangan protokol implementasi bertahap dan penelitian lanjutan tentang sistem adaptif berbasis profil kognitif.